Tripterhyponoid A from Tripterygium hypoglaucum Inhibiting MRSA by Multiple Mechanisms - Yan-Yan Zhu; Qiong Jin; Zhao-Jie Wang; Mei-Zhen Wei; Wen-Biao Zu; Zhong-Shun Zhou; Bin-Yuan Hu; Yun-Li Zhao; Xu-Jie Qin; Xiao-Dong Luo (Molecules)
The emergence of methicillin-resistant Staphylococcus aureus (MRSA) and its biofilm-forming ability underscore the limitations of current antibiotics. In this study, a new compound named tripterhyponoid A was found to effectively combat MRSA, with an MIC of 2.0 μg/mL. It inhibited biofilm formation by downregulating genes related to the quorum sensing (QS) pathway (sarA, agrA, agrB, agrC, agrD, and hld) and eradicated mature biofilms. Furthermore, it induced DNA damage by binding to bacterial DNA, enhancing its efficiency against MRSA. Therefore, its anti-MRSA properties with multiple mechanisms of action make it less prone to developing resistance over 20 days. In addition, it reduced the bacterial load and regulated the levels of inflammatory cytokines IL-6 and IL-10 at the wound site in a mouse skin infection model. This paper provides the first in-depth investigation of the mechanisms of triterpenoids against MRSA by inhibiting the expression of QS system genes and binding to DNA.